Penyuluhan Surat-Menyurat Dinas di SMKN PP Kalasey: Official Correspondence Training at SMKN PP Kalasey (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Community Service (PKM) on Official correspondence Training at SMKN PP Kalasey is a gate way for university practitioners in dedicating their knowledge toward the community, especially in the field of languages. This training is intended to provide deepen knowledge regarding the language barrier that used in correspondence activities, especially official letters. This training is carried out by using direct face-to-face communication methods. This activity is carried out by visiting PKM partners directly to find out firsthand the partner's needs regarding the use of language in official letters. It is then immediately responded by providing composition of language material in official letter, followed by letter writing simulation and evaluation. activity. As a result, PKM partners gain better understanding and ability in applying suitable and grammatical correct language composition applied in correspondence